Omnishopper: perspectiva do consumidor na adoção e integração de canais - Giannecchini, Luiz Fernando Pinheiro (2023)
In an increasingly dynamic and competitive scenario, in addition to several technological innovations, one of the phenomena that we observe in the consumer’s experience is the availability of different channels and brand touchpoints throughout the entire consumer journey, practically eliminating barriers between physical and digital environments. In this way, studies about omnichannel began to grow and in different approaches, but academic knowledge about consumer’s behavior and perspective in this experience is still a gap. This research aimed to understand and deepen the consumer experience across different channels, focusing on the adoption and integration of channels, from the perspective of the omnishopper, a consumer segment that use more than one channel throughout their consumer journey. Through a qualitative phenomenological method, applying semi structured interviews with twelve body moisturizers consumers and content analysis, it was identified relational, marketing, technological and behavioral elements both in the channel’s adoption and integration, as well as in the research stage, influence and consumer relationship with channels and brands all through this cross-channel experience. The study has schematizations and framework that can be used both in the design of the omnichannel strategy, providing a better and complete experience for consumers.